Functional properties of Phaleria macrocarpa fruit flesh at different ripeness - Ahmed Asrity, Suaad Mohamad; Tsan, Fui Ying; Ding, Phebe; Syed Ahmad, Syed Aris (Universiti Putra Malaysia, 2018)
Functional property changes in Phaleria macrocarpa fruit during ripening on tree were studied. Results showed that juice extracted from fruit flesh had low acidity and soluble solid content. Fruit acidity decreased but soluble solids increased as the fruit ripened. In terms of antioxidant content, ascorbic acid, DPPH free radical scavenging activities and total phenolic content were, however, the lowest in fully ripe fruit flesh while the unripe fruit flesh had the highest. High percentage of these antioxidants was water soluble. This study suggests that the unripe fruits should be harvested for valuable medicinal product development instead of the fully ripe fruits.